Texas in the Confederacy : an experiment in nation building - Jewett, Clayton E. (Shades of blue and gray series., 2002)
"Historians examining the Confederacy have often assumed the existence of a monolithic South unified behind the politics and culture of slavery. In addition, they have argued for the emergence of a strong central state government in the Confederacy. In Texas in the Confederacy, Clayton E. Jewett challenges these assumptions by examining Texas politics with an emphasis on the virtually neglected topic of the Texas legislature. In doing so, Jewett shows that an examination of state legislative activity during this period is essential to understanding Texas's relationship with the Indian tribes, the states in Trans-Mississippi Department, and the Confederate government."--Jacket